Detection of cultural and linguistic differential item functioning in reading assessment - Woo, Yejin; Choi, Youn-Jeng (Frontiers in Education, 2025)
This study aims to determine whether differential item functioning (DIF) occurs in the PISA 2018 reading assessment and, if so, to explore which factors, such as linguistic elements, achievement goals, and perceived reading instructions as cultural elements, contribute most significantly to its occurrence. The United States was set as the reference group, and comparisons were made with Canada, Singapore, and South Korea. Item response theory-likelihood ratio (IRT-LR), logistic regression, and Rasch Tree analyses were utilized to identify DIF. Multiple methods consistently showed that item CR551Q06 exhibited DIF. The Rasch Tree analysis revealed that linguistic rather than cultural differences were the primary contributors to DIF. Interestingly, no DIF was detected using the Rasch Tree method in the comparisons between the United States and Canada and between the United States and Singapore, in contrast to the IRT-LR and logistic regression results. The analysis highlighted translation issues as a major source of bias, suggesting that careful adaptation of assessments is crucial to reducing DIF. These findings challenge assumptions about cultural differences in educational outcomes and emphasize the need for further research using varied DIF detection methods in different cultural contexts.